Analisis Tata Kelola Pendidik pada Pendidikan Jarak Jauh dalam Perspektif Kinerja dan Kesejahteraan Tutor - Setyo Nugroho, Sapto (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study is grounded in the aim to comprehend the governance of Tutors as educators within the context of Distance Education, particularly at Universitas Terbuka, in light of the emergence of new forms of labor in the platform-based economy. The primary objective of this research is to analyze the performance and well-being of Tutors engaged in platform-mediated learning, and to examine whether their employment status reflects the characteristics typically associated with new forms of labor. Employing a qualitative descriptive method and a case study approach, data were collected through surveys, interviews, and document analysis focusing on Tutors of the Government Science Study Program. The findings indicate that Tutors perform their contractual duties with varying levels of dedication, receive their entitlements, and exhibit diverse professional backgrounds. The majority perceive the partnership system to be reasonably fair, enjoy a degree of work flexibility, and benefit from adequate technological support and training. Nonetheless, several challenges persist, particularly regarding the quality of instruction, recognition and reward systems, mechanisms for performance monitoring, and anxieties over the potential displacement of Tutors by artificial intelligence or other forms of automated reasoning. The study concludes that Tutors in Distance Education cannot yet be fully classified as new forms of labor, given their relatively stable work control and equitable partnership arrangements. However, signs of precarization remain evident, especially in relation to professional recognition and labor protection. Therefore, there is a pressing need for stronger regulatory frameworks and institutional strategies to safeguard the sustainability of the Tutor’s role within the Distance Education ecosystem.